Prenatal and postnatal bisphenol A exposure and social impairment in 4-year-old children - Youn-Hee Lim; Sanghyuk Bae; Bung-Nyun Kim; Choong Ho Shin; Young Ah Lee; Johanna Inhyang Kim; Yun-Chul Hong (BMC, 2017)
Abstract Background Prenatal and postnatal exposure to bisphenol A (BPA) may affect early brain development. Rodent studies suggest that prenatal and postnatal neurodevelopmental toxicity from BPA exposure may manifest as social deficits in offspring. We investigated the association between prenatal and postnatal exposure to BPA and social impairments in a sample of 4-year-old children. Methods We recruited second-trimester pregnant women between 2008 and 2011, and measured their creatinine-adjusted prenatal urine BPA levels. In 2014-2015, a subset of 4-year-old children born to these women underwent neurobehavioral assessment and physical examination. We collected urine and blood from the children and assessed social impairments, including deficits in social interaction, social communication, and other behavior patterns using the Korean version of the Social Communication Questionnaire (K-SCQ) (n = 304). We examined social impairments associated with prenatal exposure at mid-term pregnancy and postnatal exposure to BPA at 4 years of age, using linear and piecewise linear regression models. Results The relationship between prenatal BPA exposure and social communication was non-linear and statistically significant at or above the flexion point for BPA levels of 3.0 μg/g creatinine in girls (58.4%, 95% confidence interval [CI], 6.5% to 135.8%). Each 2-fold increase in postnatal BPA exposure was significantly associated with an 11.8% (95% CI, 0.6% to 24.3%) increase in impairment in social communication in 4-year old girls, as indicated by the linear regression model. Conclusion Prenatal and postnatal BPA exposure is associated with social impairment at 4 years of age, particularly in girls.